2015
DOI: 10.1007/s00508-015-0886-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum soluble urokinase-type plasminogen activator receptor and interferon-γ-induced protein 10 levels correlate with significant fibrosis in chronic hepatitis B

Abstract: suPAR and IP-10 were able to distinguish between significant and mild fibrosis with good sensitivity and specificity, and may thus represent useful biomarkers for identifying patients with significant fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
0
15
2
Order By: Relevance
“…IP-10 has recently been shown to be a useful biomarker for identifying patients with significant fibrosis (Sevgi et al, 2016), and IP-10 levels are associated with a decrease in ALT levels (Yoshio et al, 2016). In this study, we first measured IP-10 levels in different patient groups using peripheral blood collected before and after antiviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…IP-10 has recently been shown to be a useful biomarker for identifying patients with significant fibrosis (Sevgi et al, 2016), and IP-10 levels are associated with a decrease in ALT levels (Yoshio et al, 2016). In this study, we first measured IP-10 levels in different patient groups using peripheral blood collected before and after antiviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Without surgery, children with biliary atresia will finally die due to biliary cirrhosis and liver failure[1]. Recently, circulating uPAR levels have been shown to be involved in chronic liver disorders, including chronic hepatitis B and C, liver cirrhosis, and hepatocellular carcinoma[17-20]. Based on our experience, there is no report about circulating uPAR and hepatic fibrosis in various degrees of postoperative biliary atresia.…”
Section: Discussionmentioning
confidence: 99%
“…liver fibrosis), where elevated levels of IP-10 were detected. 37 Antonelli and colleagues demonstrated that high IP-10 values are associated with more severe clinical phenotype and with the presence of lung fibrosis in systemic sclerosis patients. 38 Markers of inflammatory activity are important for the assessment and management of chronic airway diseases with chronic inflammation and loss of lung volume, like chronic obstructive pulmonary disease (COPD).…”
Section: 13mentioning
confidence: 99%